2021
DOI: 10.24292/01.ap.174181021
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ash, maple, yew/juniper, and willow pollen seasons in the air of Kielce in 2021 in correlation with weather conditions

Abstract: The paper presents the course of ash, maple, yew, juniper, and willow pollen seasons in the city of Kielce in 2021. These are the first published aerobiological studies of these species from this city. The investigations were carried out with the volumetric method using a Lanzoni apparatus. The pollen season was determined with the method of 98% of the annual pollen grain sum. In Kielce, the highest concentrations of ash pollen (85 P/m3 of air) were recorded on April 21, maple pollen (71 P/m3) on April 28, yew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…3). A significant impact of temperature on plant pollen seasons was reported by Kizilpinar et al [43], and Ślusarczyk et al [44]. In turn, the average air humidity was strongly correlated only with the birch pollen season (in both TPS and MPS) (Tab.…”
Section: Discussionmentioning
confidence: 73%
“…3). A significant impact of temperature on plant pollen seasons was reported by Kizilpinar et al [43], and Ślusarczyk et al [44]. In turn, the average air humidity was strongly correlated only with the birch pollen season (in both TPS and MPS) (Tab.…”
Section: Discussionmentioning
confidence: 73%
“…Literature data show a significant impact of meteorological factors on the intensity of plant pollen release [24][25][26][27]. The present study demonstrated that not all meteorological factors exerted a significant effect on the pollen seasons of the analyzed plant taxa.…”
Section: Resultsmentioning
confidence: 42%
“…Moreover, the peak hornbeam pollen season in Kielce recorded on April 28 th coincided with the maximum concentration of maple pollen grains[24]. During the entire hornbeam pollen season in Kielce, the threshold value of the concentration of pollen grains (16 P/m 3 ) was exceeded on only 3 days.…”
mentioning
confidence: 85%